Electrical design of the Schneider 22kV metal-clad gas insulated switchgear (GIS) for the 2.5MW 22/0.415kV dry-type of the Singapore Sports Hub - Aguilar, Bernardo D. Jr
The project envisioned the sustainability and reliability of the electrical system in a complex sports facilities with a two incoming feeder. It is also designed to meet energy efficiency (Green Mark) as certified by Building and Construction Authority (BCA) Singapore. The main power distribution system for the facilities of the entire sports complex is based on each electro-mechanical load for each structure. Which are strategically installed and positioned and shall be utilized with cautious consideration for a safe and reliable operation, maintainability and are equipped with protection features to ensure power supply is being delivered to all loads safely and it has the flexibility of providing local isolation of supply in the event of system maintenance or repair.